KARAKTERISTIK SORPSI ISOTERMIS PADA APLIKASI SILIKA (SiO2) SEBAGAI ANTICAKING AGENT TEPUNG BUMBU - Yosra Adi Putra; Indah Yuliasih; Sugiarto (Jurnal Teknologi Industri Pertanian, 2019)
Silica dioxide is one of anticacking agent as food additive. It can be encountered in nature, especially from rice husk ash waste. The objective of this study was to obtain rice husk-based silica and find out its characteristics, then apply it in seasoned flour to examine its characteristics during the storage period based on sorption isotherm. This research consisted of two stages. The first stage was silica isolation from rice husk, it was started by washing rice husk using 5% citric acid as pre-treatment followed by 800oC combustion for 30 minutes, then continued by analyzing the characteristics of both rice husk-based silica and synthetic silica as a comparison. Last stage was formulating seasoned flour with 0.5% and 1% both rice husk-based silica and synthetic silica as anticacking agent, followed by observing the phenomenon during storage period to illustrate its sorption isotherm curve. Characterizations using XRD analysis showed both synthetic silica and rice husk-based silica hadamorphous structure. SEM-EDX analysis showed that there were 25.52% elements of C in rice husk-based silica and 10.23% of C and 1.29% of N formed in synthetic silica. Addition of both rice husk-based and synthetic silica onto seasoned flour indicated the occurrence increasing number of critical and equilibrium moisture content, water activity, and ash content. Based on characteristic of sorption isotherm curve, the 1% addition of rice husk-based silica on seasoned flour formulation gave optimum number of primary, secondary, and tertiary boundary water fractionsof 7.35%, 20.04%, 70.18%,respectively.